Impact of Return on Asset, Current Ratio, and Debt to Equity Ratio on Price with BI Rate as Moderation Variable in Mining Company - Sri Martina; Mahaitin H Sinaga; Wico Jontarudi Tarigan (Jurnal Ekuilnomi, 2024)
The study empirically analyzes the impact of Return on Asset (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on the stock price, with the BI Rate as a moderating variable. This research evaluates how these financial ratios influence stock prices and examines the moderating effect of the BI Rate on the relationship between ROA, CR, DER, and stock prices. The research period spans from 2019 to 2021, with a sample population of 20 mining companies listed on the Indonesian Stock Exchange. Data analysis is conducted using multiple linear regression methods, including F tests and T tests, and the moderating effect is tested using the residual test. The results reveal that ROA, CR, and DER significantly influence stock prices when considered together. However, only ROA has a positive effect on stock prices when considered individually, while CR and DER do not significantly impact stock prices. Additionally, the BI Rate does not moderate the relationship between ROA, CR, DER, and stock prices.